UPAYA INDONESIA DALAM MENANGKAL POTENSI INTOLERANSI DAN RADIKALISME PASCA KELOMPOK TALIBAN BERKUASA - Dina Dina; Iwan Saputra (Hubungan Internasional, 2022)
Radicalism is currently a popular issue in Indonesia after the rule of the Taliban in Afghanistan, the potential for intolerance and radicalism is increasingly becoming a very hot issue. The Indonesian government continues to take preventive measures to counter the potential phenomenon of the development of acts of intolerance and radicalism in Indonesian society after the Taliban group came to power. This has shown a condition where it is vulnerable and has the potential to return to terrorism. The Taliban created turmoil in Afghanistan. This study will explore and describe Indonesia's efforts to counter the potential for intolerance and radicalism after the Taliban came to power. The data collection method used in this study is a literature study that the author has prepared that is relevant to the title that the author is researching. Where the author will take data from news, research reports, scientific journals, and books related to the theme of this research. The results achieved in the research are Indonesia's efforts to counter the potential for intolerance and radicalism after the Taliban group came to power in Afghanistan.Keywords: Indonesia, the Taliban, radicalism and intolerance, and Pancasila